D Implementation of the Evaluation of Tale Text Learning During the Covid-19 Pandemic for Class X Students of SMA Negeri 6 Bengkulu City - Destarina, Dea; Arifin, Muhammad; Noermanzah (UNIB Press, 2022)
This research was a descriptive study on the implementation of learning evaluation which aims to describe the implementation of the evaluation of saga text learning carried out by Indonesian language teachers during the Covid-19 pandemic in class X SMA Negeri 6 Bengkulu City. The research method used was descriptive method. In accordance with the objectives of this study, the authors wanted to see how the evaluation of the learning of saga texts was carried out by Indonesian language teachers who taught in class X during the Covid-19 pandemic. The subject of this study was Mrs. Eka Darlina, M.Pd as an Indonesian teacher who carried out an evaluation of saga text learning in class X students. The data collection methods were interviews and documentation. The steps of data analysis are 1) data collection, 2) data reduction, 3) data presentation, 4) drawing conclusions. The results showed that the implementation of the evaluation of saga text learning during the Covid-19 pandemic, the teacher used online media, namely the Google Form application and Google Classroom as a medium for implementing learning evaluations, especially in saga texts. The assessment procedure prepared by the teacher by preparing the RPP and LKPD, determining the purpose of the assessment, compiling a grid, preparing the assessment instrument, delivering the results of the assessment, and the benefits of the assessment carried out in the evaluation of saga text learning. The type of learning evaluation used by the teacher is the type of formative evaluation and the evaluation tool used in the evaluation of learning was in the subjective form or questions in the form of an essay